Drug Use Review of Warfarin in Medicine Ward, Srinagarind Hospital - Lertsinudom, Sunee; Chumworathayi, Pansu; Chaiyakum, Aporanee (Srinagarind Medical Journal, 2013)
Background and objective: Warfarin has been a high alert drug due to its narrow therapeutic index. Its use review and feedback may improve the medical staffs’ service quality in efficiency and safety. Objective is to review its use in: justification for use, process indicators, complications and their managements, and outcome indicators in order to develop the institute’s proper warfarin use guideline. Methods: Warfarin use guideline was developed based on the literature review and the experts’ opinion. The drug use review of warfarin in complete medication chart was done in warfarin-using patients in medicine ward, Srinagarind Hospital, who were admitted during January 2004 and December 2007 in Srinagarind Hospital, Khon Kaen, Thailand, comparing with the guideline. Results: In a total of 85 patients, we found that 54.1% of them were female, aged 53.9 ±14.4 year-old. At the time of admission, 68% had been using warfarin, however, their INRs were within optimal range in only 16%. Ninety-five percent of the patients, the use of drug had justified indications. There were lack of necessary laboratory evaluations including hematocrit, platelet count, and ALT/AST in 14%, 16%, and 35%, respectively. There were proper starting and adjusting, when compared to proposed guideline, in 71% and 68%, respectively. There were drug interactions in 27%. On admission, major bleeding and minor bleeding were found in 10% and 9%, respectively. Outcome indicator of warfarin using (INR) met its goal in only 25%. Conclusion: Most of the warfarin use problems that we found in this study could be prevented, if proper guideline is formulated and most of these problems and their related complications could be managed. Keywords : warfarin, guideline